Production process of bar with high strength and ultralow magnetic permeability
Through high-purity raw material pretreatment and advanced smelting technology, combined with optimized hot processing and controlled rolling technology, the problems of imperfect impurity control and insufficient tissue stability in rod production are solved, and the comprehensive performance of high strength, low magnetic permeability and excellent corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411862752.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, in the production process of bars, due to imperfect impurity control and insufficient tissue stability, the material performance and uneven mechanical properties are caused.
By adopting high-purity raw material pretreatment combined with plasma arc furnace premelting technology, vacuum refining and electroslag remelting technology, optimized forging compression ratio, controlled rolling temperature and cooling rate, combined with high-efficiency solid solution treatment and rapid water cooling technology, high purity and grain refinement of the material are achieved.
It significantly improves the purity of the material and the degree of grain refinement, solves the problems of unstable performance and uneven mechanical properties, and achieves comprehensive performance of high strength, low magnetic permeability and excellent corrosion resistance.
Smart Images

Figure CN119710494A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal material processing and manufacturing, and in particular to a production process for high-strength and ultra-low magnetic permeability rods. Background Art
[0002] In the production of high-performance rods, especially for the development of materials used in high-end scenarios such as reactor screws, nuclear power equipment, and aerospace, it is usually necessary to simultaneously meet the comprehensive performance requirements of low magnetic permeability, high strength, and corrosion resistance. In traditional production processes, most of the raw materials are processed by ordinary smelting equipment, such as direct smelting in an electric arc furnace. This method has limited effect in removing gas impurities such as oxygen, hydrogen, and nitrogen, resulting in a high level of residual impurities in the material. This situation can easily lead to inclusion defects, which in turn causes fluctuations in the mechanical properties and magnetic conductivity of the rods. Although some technologies have attempted to use vacuum melting, they have not been combined with efficient deoxidation and further refining processes, and the impurity removal rate is still insufficient, affecting the consistency and stability of product performance.
[0003] Forging and rolling processes mostly use traditional temperature and deformation control parameters, and fail to optimize process parameters for grain refinement and organizational uniformity. In particular, during the controlled rolling process, the deformation rate and final rolling temperature are not fully regulated, which can easily lead to abnormal grain growth or insufficient dynamic recrystallization. This directly affects the mechanical properties and magnetic permeability of the bar, making it difficult to achieve a balance between high strength and low magnetic permeability.
[0004] Traditional rod material development usually focuses on improving a single property, such as increasing strength by increasing alloy composition, or reducing magnetic permeability by adjusting the process. However, this method often sacrifices other properties when improving a certain property. Increasing nitrogen content to reduce magnetic permeability may lead to grain boundary embrittlement.
[0005] In view of the deficiencies in the prior art, the present invention provides a production process for high-strength and ultra-low magnetic permeability rods. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a production process for high-strength and ultra-low magnetic permeability rods, which solves the problems of imperfect impurity control and insufficient structural stability in the rod production process in the prior art.
[0007] To achieve the above objectives, the present invention is implemented by the following technical solutions: a production process of high-strength ultra-low magnetic permeability rods, wherein the rods are made of the following components in mass percentage: Base iron: remainder; Chromium (Cr): 16% to 17%; Manganese (Mn): 14.2%~15.8%; Nickel (Ni): 1.0% ~ 2.0%; Nitrogen (N): 0.2%~0.045%; Carbon (C): 0.13% to 0.20%; Silicon (Si): ≤0.8%; Phosphorus (P): ≤0.045%; Sulfur (S): ≤0.025%; The oxygen content is ≤10ppm, the hydrogen content is ≤3ppm, the grain size is ≤10μm, and the magnetic permeability is U 200 ≤1.005.
[0008] Furthermore, the rod is made of 2Gr steel specially used for reactor screws. 17 Mn 14 Ni2NHA, with base iron as the main component and the balance, provides basic mechanical strength and processing performance for the rod; the chromium (Cr) content is 16% to 17%, which has a significant solid solution strengthening effect, while enhancing the corrosion resistance and oxidation resistance of the material; the manganese (Mn) content is 14.2% to 15.8%, which plays an important role in improving the deoxidation effect of the material and improving the high temperature toughness, while promoting fine grain strengthening; the nickel (Ni) content is 1.0% to 2.0%, which is used to stabilize the austenite structure, significantly reduce the magnetic permeability, and maintain high toughness in a low temperature environment; the nitrogen (N) content is 0.2% to 0.045%, which further improves the strength and corrosion resistance of the material through its solid solution strengthening effect, and at the same time improves the comprehensive performance of the material by refining the grains; the carbon (C) content is controlled at 0.13% to 0.20%, and the appropriate amount of carbon content improves the strength of the material, but through strict The silicon (Si) content is ≤0.8%, which is used to improve the deoxidation effect of the material, and at the same time, the silicon content is limited to avoid the negative impact on the magnetic permeability and organizational stability. The phosphorus (P) content is ≤0.045%, and the grain boundary embrittlement is avoided by limiting the phosphorus content, thereby improving the toughness and reliability of the material. The sulfur (S) content is ≤0.025%, and the formation of sulfide inclusions is reduced by limiting the sulfur content, thereby improving the comprehensive performance of the material. The oxygen content of the rod is controlled at ≤10ppm, and the hydrogen content is controlled at ≤3ppm. The gas impurities in the raw materials are removed through advanced pretreatment and refining processes, thereby improving the purity and performance stability of the material. The grain size is ≤10μm through electroslag remelting and controlled rolling technology, and the microstructure of the material is more uniform, thereby effectively improving the strength, toughness and durability of the material. The magnetic permeability U 200 Controlled at ≤1.005, ultra-low magnetic permeability is achieved through component design and process optimization, meeting the strict requirements of high-end application scenarios for low magnetic permeability.
[0009] Preferably, the method comprises the following steps: Raw material preparation: Select high-purity iron-based raw materials and alloy elements, and pre-treat them according to purity requirements, including drying at 120-150℃ for 4 hours and pre-melting in a plasma arc furnace; Melting and refining: The initial melting temperature is controlled at 1600-1650℃, and alloy elements are added in proportion; the nitrogen content is controlled at 0.35%-0.45% through vacuum refining treatment; the electroslag remelting (ESR) technology is used to control the cooling rate to 35℃ / min, and the grain size is ≤10μm; Hot working and controlled rolling forming: the initial forging temperature is 1150℃, and the secondary forging temperature is 1050℃; the final rolling temperature is controlled at 800℃, and rapidly cooled to 700℃ to stabilize the austenite grain structure; heat treatment and solid solution strengthening: solid solution treatment at 1050-1100℃ for 12 hours, rapid water cooling (cooling rate ≥50℃ / s) to prevent the precipitation of σ phase and Cr nitride; Subsequent processing: Use high-precision turning and grinding processes to process into the target size, ensuring the surface roughness Ra ≤ 1.0μm.
[0010] Furthermore, for raw material preparation, high-purity iron-based raw materials and alloy elements are selected, among which the purity of iron-based raw materials is ≥99%, and the purity of alloy elements such as chromium (Cr), manganese (Mn), and nickel (Ni) is above 99% to ensure the purity of the basic components of the material; in the process of raw material preparation, all alloy raw materials need to be dried at 120-150°C for 4 hours to remove moisture and volatile impurities on the surface and inside of the raw materials, thereby reducing the generation of harmful gases such as oxygen and hydrogen during the smelting process; the pretreated raw materials are pre-melted in a plasma arc furnace to effectively remove gas impurities such as oxygen, hydrogen, and nitrogen, while homogenizing the distribution of alloy elements to ensure smelting. The efficiency and uniformity of the stage are improved; in the smelting and refining stage, the initial smelting is carried out in an electric arc furnace, and the smelting temperature is strictly controlled between 1600 and 1650°C. Alloy elements are gradually added in proportion and fully stirred to ensure the uniform distribution of alloy elements; through vacuum refining technology, degassing treatment is carried out in a vacuum environment of 10^-3atm to effectively reduce the oxygen and hydrogen content in the material, especially by accurately controlling the nitrogen content in the range of 0.35% to 0.45%, ensuring that nitrogen is uniformly dissolved without causing grain boundary embrittlement; after refining, the electroslag remelting (ESR) technology is used to further purify the material, and by adding high-efficiency slag (CaF2: 30% , Al2O3:20%, CaO:50%) to reduce non-metallic inclusions, and the cooling rate is controlled at 35℃ / min during electroslag remelting, so that the final grain size is controlled at ≤10μm, achieving grain refinement and organizational uniformity; in the hot working and controlled rolling forming stage, forging is first carried out, and the initial forging temperature is controlled at 1150℃ to ensure that the alloy structure is fully plastically deformed at high temperature, and then the secondary forging temperature is 1050℃ to further improve the uniformity of the material and refine the grains through plastic deformation; in the controlled rolling stage, the final rolling temperature is strictly controlled at 800℃, and it is quickly cooled to 700℃ to stabilize the austenite grain structure and avoid dynamic recrystallization. Premature occurrence leads to abnormal grain growth; in the heat treatment and solid solution strengthening stage, solid solution treatment is carried out at 1050-1100℃ for 12 hours. The alloy elements are fully dissolved through homogenization treatment, followed by rapid water cooling (cooling rate ≥50℃ / s) to effectively prevent the precipitation of σ phase and Cr nitride, thereby ensuring the mechanical properties and corrosion resistance of the material; in the subsequent processing stage, high-precision turning and grinding processes are used to precisely process the rods, and the rod size is processed to the target specification, while ensuring that the surface roughness Ra≤1.0μm, in order to meet the strict requirements of high-end application scenarios on surface quality. The rods are special steel for reactor screws.
[0011] Preferably, the raw material is pretreated by pre-melting in a plasma arc furnace to remove oxygen, hydrogen and nitrogen impurities in the raw material, and the oxygen content is controlled to be ≤10ppm and the hydrogen content to be ≤3ppm.
[0012] Preferably, during vacuum refining, a vacuum environment of 10^-3atm is used for degassing to make nitrogen dissolve evenly and control the nitrogen content at 0.35% to 0.45%.
[0013] Preferably, the slag formula used in the electroslag remelting process is CaF2: 30%, Al2O3: 20%, CaO: 50%, the electroslag remelting temperature is 1400-1450°C, and the cooling rate is 35°C / min.
[0014] Furthermore, in the raw material pretreatment stage, plasma arc furnace pre-melting technology is adopted, and the gas impurities such as oxygen, hydrogen and nitrogen in the raw materials are effectively removed through the powerful thermal effect of the high-temperature plasma arc and the reducing environment, so that the material reaches a higher purity; during the pre-melting process, the iron-based raw materials and alloy elements are heated to a molten state under vacuum or a protective atmosphere, and the gas inclusions in the raw materials are floated and taken away from the melt through continuous stirring, thereby significantly reducing the residual oxygen and hydrogen; by optimizing the pre-melting process parameters, the oxygen content in the raw materials is controlled within the range of ≤10ppm, effectively reducing the formation of oxide inclusions, and at the same time, the hydrogen content is controlled within ≤3ppm, avoiding the generation of defects caused by hydrogen precipitation during the smelting process; preferably, in the vacuum refining stage, the residual gas impurities in the melt are further reduced by adopting a low-pressure vacuum environment of 10^-3atm, combined with efficient degassing treatment to ensure The nitrogen element is dissolved evenly in the melt, thereby avoiding the problem of grain boundary embrittlement or unstable performance caused by uneven distribution of nitrogen content; by precisely controlling the nitrogen content within the range of 0.35%, the fine grain strengthening and low magnetic permeability contribution of nitrogen are optimized, ensuring the comprehensive performance of the material; preferably, in the electroslag remelting process, a specific proportion of slag formula is adopted, in which CaF2 accounts for 30%, Al2O3 accounts for 20%, and CaO accounts for 50%. This slag formula effectively reduces non-metallic inclusions in the melt by enhancing the electrical conductivity and deoxidation ability of the slag layer; the electroslag remelting temperature is strictly controlled at 11450°C to ensure the uniformity of the melt and the activity of the slag layer. At the same time, by controlling the cooling rate within the range of 35°C / min, effective grain refinement and uniform distribution are achieved, thereby providing the material with higher strength and stable magnetic conductivity. The rod is a special steel for reactor screws.
[0015] Preferably, the forging compression ratio is ≥3:1, the grains are refined by plastic deformation, the material uniformity is improved, the final rolling temperature is controlled at 850°C, and the steel is rapidly cooled to 700°C.
[0016] Preferably, the solution treatment temperature is 1050-1100° C., the temperature is kept for 12 hours, and the cooling rate during rapid water cooling is ≥50° C. / s to avoid precipitation of σ phase and Cr nitride.
[0017] Preferably, the tensile strength of the rod is 600 MPa, the yield strength is 400 MPa, and the impact energy is ≥50 J at -40°C.
[0018] Preferably, the corrosion resistance is tested by a 240-hour salt spray test using a 5% NaCl solution, and the corrosion weight loss is ≤0.005 g / cm².
[0019] Furthermore, in the hot working and controlled rolling forming stage, the grain structure of the bar is effectively refined through a plastic deformation process with a forging compression ratio of ≥3:1, while eliminating segregation and porosity inside the material, significantly improving the uniformity and density of the material; after forging, the final rolling temperature is strictly controlled at 850°C, and controlled rolling within this temperature range can stabilize the austenite grain structure and avoid abnormal grain growth caused by premature dynamic recrystallization; after rolling, the bar temperature is rapidly reduced to 700°C by rapid cooling, and this cooling process can inhibit the formation of precipitates during the phase change process, thereby maintaining the stability and uniformity of the material structure; preferably, in the heat treatment stage, the bar undergoes a solution treatment process, wherein the solution treatment temperature is strictly controlled between 1050 and 1100°C, and the temperature is kept for 12 hours to ensure sufficient dissolution of the alloy elements. solution and uniform distribution; after solution treatment, a rapid water cooling process is adopted, and the cooling rate is ≥50℃ / s. This rapid cooling process can effectively avoid the precipitation of σ phase and Cr nitride, thereby preventing the toughness of the rod from decreasing and the performance degradation; preferably, the rod prepared by the above process exhibits excellent mechanical properties, wherein the tensile strength reaches 600MPa, the yield strength reaches 400MPa, and it can still maintain good toughness in a low temperature environment, and the impact energy is ≥50J under -40℃ conditions, which meets the special requirements of high-end application scenarios for low-temperature toughness; preferably, in the corrosion resistance test, the rod passes the 240-hour salt spray test of 5% NaCl solution, and its corrosion weight loss is ≤0.005g / cm², which indicates that the rod has excellent corrosion resistance and can be used for a long time in harsh environments and maintain stable performance.
[0020] Preferably, the rod is suitable for high-performance reactor screws, nuclear power plants, aerospace and high-end machinery manufacturing fields.
[0021] The present invention provides a production process for high-strength and ultra-low magnetic permeability rods. It has the following beneficial effects: 1. The present invention further reduces harmful gas impurities such as oxygen, hydrogen, and nitrogen in the raw materials by using high-purity raw material pretreatment combined with plasma arc furnace premelting technology, and makes the alloy composition distribution more uniform through vacuum refining and electroslag remelting processes. The technical effect of improving material purity and grain refinement is achieved. Compared with the solution in the prior art that only relies on traditional smelting processes and is difficult to effectively remove impurities, the problem of unstable material properties and easy inclusion defects after processing is solved. The rod is 2Gr17Mn14Ni2NHA, a special steel for reactor screws.
[0022] 2. The present invention significantly improves the structural stability and mechanical properties of the material by optimizing the forging compression ratio, controlled rolling temperature and cooling rate, combined with efficient solution treatment and rapid water cooling process. The technical effect of achieving low magnetic permeability while having high strength and excellent toughness is achieved. Compared with the problems of grain growth and uneven performance caused by unreasonable controlled rolling process in the prior art, the defects of insufficient durability and reliability of bars in complex application scenarios are solved.
[0023] 3. The present invention combines ultra-low magnetic permeability, high strength and excellent corrosion resistance through systematic component design and process optimization, achieving an optimal balance between multiple properties. It achieves the technical effect of meeting the special needs of high-performance equipment. Compared with the technical solutions in the prior art that cannot take into account low magnetic permeability, high strength and corrosion resistance at the same time, it solves the problem of insufficient adaptability of materials in the application of reactors. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Please refer to the attached Figure 1 : Example 1: Innovative ingredients and process parameters are within the range of values Steps and process parameters: Raw materials preparation: Iron-based raw materials (purity ≥99%), Cr (16.5%), Mn (15%), Ni (1.5%), N (0.35%), C (0.15%), Si (0.5%), P (0.03%), and S (0.02%).
[0027] Dry at 120℃ for 4 hours, pre-melt in a plasma arc furnace to remove oxygen (≤10ppm) and hydrogen (≤3ppm).
[0028] Smelting and Refining: Electric arc furnace smelting, the temperature is controlled at 1600 ~ 1650 ℃, and the addition ratio is strictly controlled.
[0029] After vacuum refining (10^-3atm), the nitrogen content is evenly distributed and the total nitrogen content is 0.35%.
[0030] Electroslag remelting, slag ratio CaF2: 30%, Al2O3: 20%, CaO: 50%, cooling rate 35℃ / min, grain size is about 8μm.
[0031] Hot working and controlled roll forming: The primary forging temperature is 1150°C, the secondary forging temperature is 950°C, and the forging compression ratio is 4:1.
[0032] The controlled rolling temperature was 820°C and the cooling rate was maintained under rapid water cooling conditions.
[0033] Heat treatment and subsequent processing: Solution treatment at 1050℃ for 12 hours, water cooling rate ≥50℃ / s.
[0034] Using high-precision turning and grinding, the surface roughness Ra ≤ 1.0μm.
[0035] Technical effects: The material has uniform grains, good organizational stability and optimal comprehensive performance.
[0036] Example 2: Innovation point: The ingredients are below the range and the process parameters are low Steps and process parameters: Raw materials preparation: Iron-based raw materials (purity ≥98.5%), Cr (16%), Mn (14%), Ni (1.0%), N (0.25%), C (0.12%), Si (0.6%), P (0.04%), and S (0.03%).
[0037] The drying temperature is 100°C, and the pre-melting is carried out in an ordinary furnace to remove oxygen (≤15ppm).
[0038] Smelting and Refining: Electric arc furnace smelting, the temperature is controlled at 1550 ~ 1600 ℃.
[0039] Vacuum refining (10^-2atm), the nitrogen content is unevenly distributed, and the total nitrogen content is 0.25%.
[0040] Hot working and controlled roll forming: The primary forging temperature is 1100°C, the secondary forging temperature is 900°C, and the forging compression ratio is 3:1.
[0041] The controlled rolling temperature is 780℃ and the cooling rate is slow.
[0042] Heat treatment and subsequent processing: Solution treatment at 1030℃ for 8 hours, cooling rate ≤40℃ / s.
[0043] Technical effects: The material grains are relatively coarse, the structure is not stable enough, and the magnetic permeability and strength are low.
[0044] Example 3: Innovative ingredients above the range and process parameters are high Steps and process parameters: Raw materials preparation: Iron-based raw materials (purity ≥99.5%), Cr (17%), Mn (15.8%), Ni (2.0%), N (0.4%), C (0.2%), Si (0.7%), P (0.04%), and S (0.02%).
[0045] Dry at 150℃ for 5 hours, pre-melt in plasma arc furnace to remove oxygen (≤8ppm).
[0046] Smelting and Refining: Electric arc furnace smelting, the temperature is controlled at 1650 ~ 1700 ℃.
[0047] Vacuum refining (10^-4atm), nitrogen content up to 0.4%.
[0048] Hot working and controlled roll forming: The primary forging temperature is 1200℃, the secondary forging temperature is 1000℃, and the forging compression ratio is 5:1.
[0049] The controlled rolling temperature is 860°C and the cooling rate is extremely fast (ultra-fast cooling).
[0050] Heat treatment and subsequent processing: Solution treatment at 1100℃ for 16 hours, cooling rate ≥60℃ / s.
[0051] Technical effect: The grain refinement is obvious, but the high nitrogen content leads to grain boundary embrittlement and reduced corrosion resistance.
[0052] Comparative experiment Comparative Example 1: Lack of innovative ingredient 1 (low Cr content) The Cr content in the raw material is 10%, the proportions of other components are the same, and the process parameters are consistent with those in Example 1.
[0053] Comparison results: The material has coarse grains, uneven structure and significantly reduced corrosion resistance.
[0054] Comparative Example 2: Lack of innovative ingredient 2 (low N content) The N content in the raw material is 0.1%, the proportions of other components are the same, and the process parameters are consistent with those in Example 1.
[0055] Comparison results: The magnetic permeability of the material is significantly increased, while the mechanical properties are reduced.
[0056] Comparative Example 3: Using traditional technology Conventional arc furnace smelting, without vacuum refining and electroslag remelting, other parameters are consistent with Example 1.
[0057] Comparison results: The material has many inclusions, coarse grains and deteriorated overall performance.
[0058] Experimental data table Table 1: Material purity and grain refinement effect Instance Number Oxygen content (ppm) Hydrogen content (ppm) Grain size (μm) Uniformity of impurity content Example 1 ≤10 ≤3 ≤8 excellent Example 2 ≤15 ≤5 ≤12 generally Example 3 ≤8 ≤2 ≤6 excellent Comparative Example 1 ≤20 ≤8 ≤15 Difference Table 2: Tissue stability and mechanical properties Instance Number Tensile strength (MPa) Yield strength (MPa) Toughness (J) Tissue homogeneity Example 1 680 370 55 excellent Example 2 590 320 40 generally Example 3 700 400 50 good Comparative Example 2 560 310 35 Difference Table 3: Magnetic permeability and corrosion resistance Instance Number Magnetic permeability (U200) Corrosion weight loss (g / cm²) Comprehensive performance Example 1 ≤1.005 ≤0.005 excellent Example 2 ≤1.015 ≤0.010 generally Example 3 ≤1.003 ≤0.008 good Comparative Example 3 ≤1.020 ≤0.015 Difference The present invention significantly improves the comprehensive performance of high-strength and ultra-low magnetic permeability rods by optimizing material composition design and systematic process flow. The experimental results of the embodiments show that the present invention has achieved technical breakthroughs in the following aspects: Material purity and grain refinement The use of high-purity raw material pretreatment, vacuum refining and electroslag remelting processes has significantly reduced the content of harmful impurities such as oxygen and hydrogen, achieved grain refinement and improved distribution uniformity, and solved the problems of many inclusions and uneven structure in the existing technology.
[0059] Tissue stability and mechanical properties By optimizing the hot processing and controlled rolling forming processes and combining efficient solution treatment and rapid cooling technology, the mechanical properties of the rods are improved, achieving an organic combination of low magnetic permeability, high strength and toughness, and solving the problem of poor performance uniformity caused by unstable organization in the existing technology.
[0060] Optimal balance of comprehensive performance The present invention successfully establishes a performance balance between ultra-low magnetic permeability, high strength and excellent corrosion resistance, which significantly improves the adaptability of the material in high-end fields such as reactor screws, nuclear power plants and aerospace, and overcomes the problem of single performance optimization leading to degradation of other properties in the prior art.
[0061] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A production process for high-strength and ultra-low magnetic permeability rods, characterized in that: The rod is made of the following components in percentage by mass: Base iron: remainder; Chromium (Cr): 16% to 17%; Manganese (Mn): 14.2%~15.8%; Nickel (Ni): 1.0% ~ 2.0%; Nitrogen (N): 0.2%~0.045%; Carbon (C): 0.13% to 0.20%; Silicon (Si): ≤0.8%; Phosphorus (P): ≤0.045%; Sulfur (S): ≤0.025%; The oxygen content is ≤10ppm, the hydrogen content is ≤3ppm, the grain size is ≤10μm, and the magnetic permeability U200 is ≤1.
005.
2. The production process of a high-strength ultra-low magnetic permeability rod according to claim 1, characterized in that: The following steps are involved: Raw material preparation: Select high-purity iron-based raw materials and alloy elements, and pre-treat them according to purity requirements, including drying at 120-150℃ for 4 hours and pre-melting in a plasma arc furnace; Melting and refining: The initial melting temperature is controlled at 1600-1650℃, and alloy elements are added in proportion; the nitrogen content is controlled at 0.35%-0.45% through vacuum refining treatment; the electroslag remelting (ESR) technology is used to control the cooling rate to 35℃ / min, and the grain size is ≤10μm; Hot working and controlled rolling forming: the initial forging temperature is 1150℃, and the secondary forging temperature is 1050℃; the final rolling temperature is controlled at 800℃, and rapidly cooled to 700℃ to stabilize the austenite grain structure; heat treatment and solid solution strengthening: solid solution treatment at 1050-1100℃ for 12 hours, rapid water cooling (cooling rate ≥50℃ / s) to prevent the precipitation of σ phase and Cr nitride; Subsequent processing: Use high-precision turning and grinding processes to process into the target size, ensuring the surface roughness Ra ≤ 1.0μm.
3. The production process of a high-strength ultra-low magnetic permeability rod according to claim 1, characterized in that: Raw material pretreatment is performed by pre-melting in a plasma arc furnace to remove oxygen, hydrogen and nitrogen impurities in the raw materials, and the oxygen content is controlled to be ≤10ppm and the hydrogen content to be ≤3ppm.
4. The production process of a high-strength ultra-low magnetic permeability rod according to claim 1, characterized in that: During vacuum refining, a vacuum environment of 10^-3atm is used for degassing to make the nitrogen dissolve evenly and control the nitrogen content at 0.35% to 0.45%.
5. The production process of a high-strength ultra-low magnetic permeability rod according to claim 1, characterized in that: The slag formula used in the electroslag remelting process is CaF2: 30%, Al2O3: 20%, CaO: 50%, the electroslag remelting temperature is 1400-1450°C, and the cooling rate is 35°C / min.
6. The production process of a high-strength and ultra-low magnetic permeability rod according to claim 1, characterized in that: The forging compression ratio is ≥3:
1. The grains are refined through plastic deformation to improve the uniformity of the material. The final rolling temperature is controlled at 850℃ and rapidly cooled to 700℃.
7. The production process of a high-strength and ultra-low magnetic permeability rod according to claim 1, characterized in that: The solution treatment temperature is 1050-1100°C, and the temperature is kept for 12 hours. The cooling rate during rapid water cooling is ≥50°C / s to avoid the precipitation of σ phase and Cr nitride.
8. The production process of a high-strength and ultra-low magnetic permeability rod according to claim 1, characterized in that: The tensile strength of the rod is 600MPa, the yield strength is 400MPa, and the impact energy is ≥50J at -40℃.
9. The production process of a high-strength and ultra-low magnetic permeability rod according to claim 1, characterized in that: The corrosion resistance has passed the 240-hour salt spray test of 5% NaCl solution, and the corrosion weight loss is ≤0.005g / cm².
10. The production process of a high-strength and ultra-low magnetic permeability rod according to claim 1, characterized in that: The rod is suitable for high-performance reactor screws, nuclear power plants, aerospace and high-end machinery manufacturing fields.
Citation Information
Patent Citations
Cr30Ni70Nb bar material and fabrication process thereof
CN109055822A
Manufacturing method of iron-nickel-chromium-based corrosion-resistant alloy hot-rolled bar for nuclear power evaporator
CN112553518A
High-toughness nickel-iron-based heat-resistant alloy for high-temperature gas cooled reactor and preparation method thereof
CN117626059A
Nickel-based alloy bar with excellent high-temperature performance and extremely low gas content and manufacturing method
CN118685662A
Method for manufacturing steel article having high magnetic permeability and low coercive force
US5073211A